Similar effectiveness of Fab and F(ab')2 antivenoms in the neutralization of hemorrhagic activity of Vipera berus snake venom in mice - Lomonte, Bruno (1996)
The ability of two antivenoms to Vipera spp., consisting of Fab (Therapeutic Antibodies), or of F(ab′)2 (Zagreb Institute of Immunology) antibody fragments, to neutralize the hemorrhagic activity of Vipera berus snake venom in mice, was compared. First, the neutralizing potency was determined by in vitro preincubation of venom and antivenom, followed by intradermal injection into mice and subsequent measurement of the hemorrhagic area. Both antivenoms had the same anti-hemorrhagic potency, in terms of volume of antivenom/mass of venom, with an estimated ed50 (50% reduction of the effect) of 80 μl antivenom/mg venom. Therefore, no adjustments in dose were necessary for subsequent in vivo comparative experiments. When the antivenoms were administered intravenously into mice immediately after intradermal venom injection, there was no difference in their effectiveness in reducing hemorrhagic lesions, at all doses tested. These results indicate that neutralization of local hemorrhagic activity of V. berus venom in vivo is not improved by the use of the smaller Fab fragments, in comparison to F(ab′)2, when equivalent neutralizing units are injected. However, this does not exclude the possibility that other clinically relevant venom effects may be neutralized with different efficiency by Fab or F(ab′)2 fragments of antibodies.